Juridical Review Of The Customary Sale And Purchase Of Land In Kalisalak Village, Limpung District, Batang District - Sihotang, Amri Panahatan; Udianto, Udianto - (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
A reform intended to ensure legal certainty and improve the quality of evidence is the sale and purchase of land, which was previously sufficient to be completed in the presence of the village head but now needs to be completed in the presence of the PPAT per land regulations. The issue at hand pertains to the proper methods for purchasing and disposing of customary land within Kalisalak village, as well as the challenges that may arise. This study employed an empirical juridical research design with analytical descriptive research criteria. The study's findings indicate that, despite certain barriers to customary land purchasing and selling, the community's continued practice of land transactions based on custom is still permitted as long as the "cash" and "clear" requirements are satisfied. To avoid disputes in the sale and purchase of land, the government must provide clearer regulations for oversight and implementation. Additionally, legal knowledge about these restrictions must be widely distributed. In order to acquire legal clarity regarding land rights, the PTSL program significantly benefits the community and makes obtaining property certificates simple. This research suggests that in order for current legislation to be relevant to current trends, the government should evaluate its customary land regulations